Male and Female Special Education Teachers' Perceptions of Gender Roles: A Comparative Analysis in the context of Nepal - Shrestha, Sharan Hari; Rai, Smriti (Pragya Darshan प्रज्ञा दर्शन, 2025)
This study aimed to compare the perspectives of male and female teachers regarding gender biasness. It focused on special education teachers in Kathmandu, Nepal and it was conducted through a quantitative method with survey design. 70 participants were chosen through convenience sampling method from seven special education schools. The survey instrument consisted of a Likert-scale type questionnaire consisting of 20 statements in 4 main areas i.e. biological, mental, and emotional-behavioral and teacher's role regarding gender issues. The results displayed that teachers are gender biased in three main areas which are: biological, mental and emotional-behavioral aspects of gender.